Complexity in Linear Systems: A Chaotic Linear Operator on the Space of Odd 2π-Periodic Functions - Tamás Kalmár-Nagy; Márton Kiss (Complexity)
Not just nonlinear systems but infinite-dimensional linear systems can exhibit complex behavior. It has long been known that twice the backward shift on the space of square-summable sequences l2 displays chaotic dynamics. Here we construct the corresponding operator C on the space of 2π-periodic odd functions and provide its representation involving a Principal Value Integral. We explicitly calculate the eigenfunction of this operator, as well as its periodic points. We also provide examples of chaotic and unbounded trajectories of C.